1984
DOI: 10.1111/j.1365-2621.1984.tb12830.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Gelation of Selected Comminuted Muscle Systems–Rheological Changes during Processing, Final Strengths and Microstructure

Abstract: Sols were prepared from cornminuted fish (surimi), beef, pork and turkey muscles. Continuous evaluation of changes in structural rigidity and energy damping during heating of the sols from 3" to 95°C was performed in a nondestructive, temperature-controlled Thermal Scanning Rigidity Monitor. Surimi presented major rigidity transitions at 40". 48" and 65°C; beef at 43". 56" and 69°C; pork at 44", 53" and 69°C; and turkey at 50", 53" and 79'C. All materials exhibited rapid decrease in energy damping (i.e. increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(73 citation statements)
references
References 4 publications
8
63
1
1
Order By: Relevance
“…At this point, the sol had turned to a viscoelastic gel. The heating curve obtained with CBM is typical for poultry meat (Montejano, 1984). The control group had a lower initial G′ value than other raw batters, due to it has lower salt soluble protein (Table 1) and different composed of type fibre.…”
Section: Resultsmentioning
confidence: 90%
“…At this point, the sol had turned to a viscoelastic gel. The heating curve obtained with CBM is typical for poultry meat (Montejano, 1984). The control group had a lower initial G′ value than other raw batters, due to it has lower salt soluble protein (Table 1) and different composed of type fibre.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, excess attractive strength cause coagulation, and excess repulsive strength causes dissolution of the network's structure. Montejano et al (1984) reported that the rigidity of the eggwhite started at 71°C and increased at 83°C, and the elasticity developed between 70 and 74°C. Denaturation of ovalbumin occurred from 79°t o 84°C.…”
Section: Gelationmentioning
confidence: 99%
“…A preparação das amostras seguiu o procedimento de MONTEJANO, HAMANN & LANIER [17]. Claras de 10 ovos foram homogeneizadas por 5 minutos com agitador magnético na velocidade mínima, para prevenir a formação de bolhas de ar.…”
Section: -Análise Do Perfil De Texturaunclassified